MENTRADISIKAN KRITIK TAFSIR: UPAYA MERETAS MATA RANTAI ABSOLUTISME PENAFSIRAN - Adang Kuswaya ; MK Ridwan (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2018)
This paper aims to provide insight and new perspectives in cutting the chain of absolutism interpretation through tradition criticism interpretation that emphasizes the values of objectivity, comprehensiveness, scientific and systematic. Because in reality absolutism interpretation still becomes mainstream among the general public even an interpreter generation. Absolutism of interpretation becomes one of dangerous threat which can lead to stagnation of the science and the obstacle of civilization. Whereas interpretation is no more just a product of the times and continuous process in exploring the meanings of the Qur'an. So there is no ‘final word’ in an interpretation. To answer the problem, this reseach uses science philosophy approach as its analysis tools. In conclusion, there are at least four operational steps in carrying out the work criticism interpretation that boils down to the region of the ontology, epistemology, and axiology i.e; Firstly, the critic must first understand the substance of exegesis interpretation as process and interpretation as product. Secondly, understand the construction criticism interpretation are the historicity of criticism, the base of criticism, the purpose of criticism, as well as the principles and parameters of criticism. Thirdly, start working criticism interpretation with two work areas that are criticism intrinsic and criticism extrinsic. Fourthly, give the review and assessment of the object of study of criticism that is good (mahmud) and feasible to use (maqbul), or deviate (munharif) and not unworthy to use (mardud).